Retrospective cohort study of pregnancy terminations before the 24th week of pregnancy - Ömeroğlu, İbrahim and Sever, Barış and Gölbaşı, Hakan and Çakır, Zübeyde and Özer, Mehmet and Yıldırım, Alkım (Journal of Surgery and Medicine, 2021)
Background/Aim: Termination, which indicates ending the pregnancy process, should be performed in fetal anomalies incompatible with life or maternal-life threatening pregnancies. Pregnancy termination involves a challenging process for both the clinician and the patients. Identifying the pathology indicating termination and sharing this decision with the family should include certain strategies. In this study, the indications for termination decision were examined. We think that these indications may help the clinician make a termination decision. Methods: In this retrospective cohort study, the indications, and termination procedures performed on 707 pregnant women in the Perinatology clinic of Izmir Tepecik Training and Research Hospital between November 2016 and November 2020 were analyzed retrospectively. Results: The total number of patients who underwent termination was 707. Their ages varied between 14 and 45 years (median 29.6). The median number of pregnancies among all patients was 2.5 (range: 1-12). The minimum and maximum gestational weeks of termination were 10 and 24 weeks, respectively (median 17.4). Termination indications were divided into groups: a) Congenital malformations (without karyotype diagnosis) (n=400, 56.5%) b) Congenital malformation with diagnosed karyotype anomalies (n=27, 3.8%) c) Only karyotype anomalies (n=146, 20.6%) d) Other fetal / obstetric disorders (anhydramnios, Preterm Premature Rupture of Membranes (PPROM), teratoma, Twin-to-twin transfusion syndrome (TTTS), drug use (n=115, 16.2%) e) Maternal causes (n=19, 2.6%). In addition, each group was divided into three groups according to the weeks of termination as 11-14 weeks, 15-22 weeks, and 23-24 weeks. The total number of patients for these groups were 170, 503 and 34, respectively. Patients without fetuses with karyotype anomalies and who were terminated due to congenital malformations were grouped according to the origin of the malformation: a) Central nervous system anomalies (57.2%) b) Multiple anomalies (18.7%) c) Hydrops fetalis (8%) d) Urinary system anomalies (6.5%) e) Skeletal system anomalies (5.7%) f) Cardiac anomalies (1.7%) g) Conjoined twins (1%) h) Congenital pulmonary airway obstruction (0.5%) i) Congenital diaphragmatic hernia (0.2%). Conclusion: The continuation of abnormal pregnancies brings many problems. Termination of pregnancies that are incompatible with life or involving serious anomalies is necessary in most cases. In daily practice, making the decision of termination and sharing it with the family should include an important algorithm.